Communication—A Unified Approach to Urban Modeling - Brotchie, J. F.; Lesse, P. F. (Management Science, 1979)
This is a report of progress in the development of a new generation of urban land use-transport models which represent an approach to a unified theory of urban land use and transport decisions. They have a common basis of economic-utility theory and entropy-information theory.